2018
DOI: 10.1155/2018/6763057
|View full text |Cite
|
Sign up to set email alerts
|

Self-Nanoemulsifying Drug Delivery System of Tetrandrine for Improved Bioavailability: Physicochemical Characterization and Pharmacokinetic Study

Abstract: The main purpose of this study was to investigate the potential of self-nanoemulsified drug delivery system (SNEDDS) to improve the oral bioavailability of tetrandrine (Tet). SNEDDS was developed by using rational blends of excipients with good solubilizing ability for Tet which was selected based on solubility studies. Further ternary phase diagram was constructed to determine the self-emulsifying region. The optimal formulation with the best self-nanoemulsified and solubilization ability consisted of 40% (w/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…Size and load can also be modulated for intracellular delivery [37,38]. Previous reports indicated that drug delivery at a higher drug concentration (improved bioavailability) was achieved by loading the drug into SNEDDS formulations [28,39]. The evaluation of the prepared formulations for visual assessment showed the spontaneous formation of clear to slightly clear emulsions with globule sizes in the nano-range [40].…”
Section: Formulation and Characterization Of Tdl-pso Sneddsmentioning
confidence: 99%
“…Size and load can also be modulated for intracellular delivery [37,38]. Previous reports indicated that drug delivery at a higher drug concentration (improved bioavailability) was achieved by loading the drug into SNEDDS formulations [28,39]. The evaluation of the prepared formulations for visual assessment showed the spontaneous formation of clear to slightly clear emulsions with globule sizes in the nano-range [40].…”
Section: Formulation and Characterization Of Tdl-pso Sneddsmentioning
confidence: 99%
“…The average droplet size of tetrandine SNEDDS was 19.75 nm. The composition of SNEDDS formulation in this research consists of 40% (w/w) oleic acid as oil, 15% (w/w) SPC, and 30% (w/w) cremophor RH-40 as surfactant, and 15% (w/w) PEG400 as cosurfactant [21].…”
Section: Characterizations Of Snedds Of Extract Singawalang Leavesmentioning
confidence: 99%
“…Emulsions produced with particle sizes <100 nm increase the solubility of hydrophobic drugs and increase their absorption. SNEDDS is an isotropic mixture of oil, surfactants, and cosurfactants that form oil-in nanoemulsions in fine water, in mild agitation, followed by administration into aqueous media, such as gastrointestinal fluids [14].…”
Section: Introductionmentioning
confidence: 99%
“…Tetrandrine has been reported to be poorly soluble (saturation is 0.015 mg/ml in phosphate buffered saline at pH 7.4), and to have low and variable oral bioavailability (cited in [20], and references therein). Pharmaceutical methods have thus been investigated to improve the bioavailability; including lipid nanocapsules, nanoparticles, ethosomes, and microspheres [20]. Tetrandrine has also been administered by inhalation in humans with a metered dose inhaler for the treatment of asthma (reviewed in [21], original not available).…”
Section: Administration and Dosagementioning
confidence: 99%
“…Administration in mice of 30 mg/kg tetrandrine intraperitoneally, a frequently-used dose in animal studies, was shown to give a peak plasma concentration of 2 μM (1.2 μg/ml) [22], whilst 10 mg/kg of oral tetrandrine resulted in a peak plasma concentration of 500 ng/ml in rats [20]. If the drug was emulsified, the same dose gave a peak concentration of 1.2 μg/ml [20]. Pharmacodynamic studies in human subjects [23] showed that a single oral dose of 100 mg tetrandrine produced an average maximal serum concentration of 67.26 ng/ml (n = 6).…”
Section: Administration and Dosagementioning
confidence: 99%